2016 IEEE 18th International Conference on E-Health Networking, Applications and Services (Healthcom) 2016
DOI: 10.1109/healthcom.2016.7749469
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things in sleep monitoring: An application for posture recognition using supervised learning

Abstract: Abstract-In this paper, we propose an Internet of Things (IoT) system application for remote medical monitoring. The body pressure distribution is acquired through a pressure sensing mattress under the person's body, data is sent to a computer workstation for processing, and results are communicated for monitoring and diagnosis. The area of application of such system is large in the medical domain making the system convenient for clinical use such as in sleep studies, non or partial anesthetic surgical procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…He also ensures hi k b he hel f C he Coefficient, the value of the coefficient is .866 which means high accuracy of detection. He also revealed that purpose of this work was to reduce storage requirement and cost on computation [8].…”
Section: Literature Reviewmentioning
confidence: 95%
“…He also ensures hi k b he hel f C he Coefficient, the value of the coefficient is .866 which means high accuracy of detection. He also revealed that purpose of this work was to reduce storage requirement and cost on computation [8].…”
Section: Literature Reviewmentioning
confidence: 95%
“…He also ensures his work by the help of Cohen's Coefficient, the value of the coefficient is .866 which means high accuracy of detection. He also revealed that purpose of this work was to reduce storage requirement and cost on computation [8].…”
Section: Literature Reviewmentioning
confidence: 95%
“…The computers process the data and do the analytical parts and stores locally. There are two things we need to focus on in this module, i.e., Processing power and the size of the hardware [39]. How much local storage do we need?…”
Section: Data Processingmentioning
confidence: 99%